Sagot :
Evaluate the expression: -15 - (+12) + (-7) = -34
Answer: B. -34
[tex]Follow\:the\:PEMDAS\:order\:of\:operations:[/tex]
[tex]\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:\:[/tex]
[tex]-15 - (+12) = -27[/tex]
[tex]= -27 + (-7)[/tex]
[tex]\mathrm{Apply\:rule\:}+\left(-a\right)\:=\:-a[/tex]
[tex]+(-7) = -7[/tex]
[tex]=-27-7[/tex]
[tex]= -27 - 7 = -34[/tex]
= [tex]-34[/tex]
Final Answer: -34
Hope It Helps with this solution! :)
Pa-Brainliest po and thanks for the points.
#Lets Study